The Effect of Gas Flow on Plasma Parameters Induced by Microwave (Baghdad Science Journal, 2018)
In this paper, construction microwaves induced plasma jet(MIPJ) system. This system was used to produce a non-thermal plasma jet at atmospheric pressure, at standard frequency of 2.45 GHz and microwave power of 800 W. The working gas Argon (Ar) was supplied to flow through the torch with adjustable flow rate by using flow meter, to diagnose microwave plasma optical emission spectroscopy(OES) was used to measure the important plasma parameters such as electron temperature (Te), residence time (Rt), plasma frequency (?pe), collisional skin depth (?), plasma conductivity (?dc), Debye length(?D). Also, the density of the plasma electron is calculated with the use of Stark broadened profiles